2017
DOI: 10.5578/tt.22093
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis masked by immunodeficiency: a review of two cases diagnosed with chronic granulomatous disease

Abstract: Tuberculosis masked by immunodeficiency: a review of two cases diagnosed with chronic granulomatous disease Chronic granulomatous disease (CGD) is a genetically heterogeneous primary immunodeficiency that is characterized by recurrent and life-threatening infections resulting from defects in phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase system and granuloma formation due to increased inflammatory response. The most commonly involved organs are the lungs, skin, lymph nodes, and liver due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Chest computed tomography (CT) plays an irreplaceable role in lung disease, and the pulmonary manifestations can be used to evaluate the patient’s condition for PIDs and PTB ( 11 ). Some studies have shown that there are differences in PTB between immunocompromised and immunocompetent patients, such as the distribution and pattern of lesions ( 12 - 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chest computed tomography (CT) plays an irreplaceable role in lung disease, and the pulmonary manifestations can be used to evaluate the patient’s condition for PIDs and PTB ( 11 ). Some studies have shown that there are differences in PTB between immunocompromised and immunocompetent patients, such as the distribution and pattern of lesions ( 12 - 14 ).…”
Section: Introductionmentioning
confidence: 99%